2014
DOI: 10.1007/jhep03(2014)043
|View full text |Cite
|
Sign up to set email alerts
|

Heat kernels on the AdS2 cone and logarithmic corrections to extremal black hole entropy

Abstract: We develop new techniques to efficiently evaluate heat kernel coefficients for the Laplacian in the short-time expansion on spheres and hyperboloids with conical singularities. We then apply these techniques to explicitly compute the logarithmic contribution to black hole entropy from an N = 4 vector multiplet about a Z N orbifold of the nearhorizon geometry of quarter-BPS black holes in N = 4 supergravity. We find that this vanishes, matching perfectly with the prediction from the microstate counting. We also… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(82 citation statements)
references
References 51 publications
1
81
0
Order By: Relevance
“…This will be our main new technical result. As a check, we shall match the small t expansion of the spinor kernel with the general form of asymptotic expansion of spinor heat kernel on a conical singularity in [24] and also show that in the special case of κ = 1/n corresponding to AdS 2 /Z n orbifold it agrees with the result in [18].…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…This will be our main new technical result. As a check, we shall match the small t expansion of the spinor kernel with the general form of asymptotic expansion of spinor heat kernel on a conical singularity in [24] and also show that in the special case of κ = 1/n corresponding to AdS 2 /Z n orbifold it agrees with the result in [18].…”
Section: Introductionmentioning
confidence: 59%
“…The special case of κ = 1/n corresponds to the Z n orbifold of AdS 2 which is obtained by identification φ = φ + 2π n . The analog of the Sommerfeld formula for orbifolds is equivalent to the summation over images expression discussed in [18]. There it was found that the small t expansion of the heat kernel for a massless scalar Laplacian on AdS 2 /Z n is given by…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gauge symmetries (including diffeomorphism invariance) further complicate the situation by introducing ghost sectors that can be quite nontrivial. The logarithmic corrections to black holes were developed in many recent works including [7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…By computing the path integration, the proposal of the quantum entropy function has been tested. Perturbative calculation on a classical saddle point and comparing it with the similar expansion on the microscopic side has led to perfect match of logarithmic correction in case of BPS black hole in N = 4 and N = 8 supergravities [21][22][23][24] in 4-dimensions and BMPV black hole in 5-dimensions [25].…”
Section: Jhep11(2015)197mentioning
confidence: 94%